Patterns of Preferences and Audience Segmentation of Kiswahili Language Radio Broadcasts in Kenya: An Analysis of Content and Demographic issue - Mogambi, Hezron (Airlangga University, 2024)
This sought to analyze patterns of consumption of Kiswahili language radio broadcasts in Kenya focusing on the demographic preferences of radio audiences in Kenya. The study used the uses and gratification and cultural imperialism theory as guides. Descriptive research design was used with both quantitative and qualitative used. The study targeted 357 respondents whose ages were between 20 and 65 who listened to Kiswahili radio programs for quantitative data. Also targeted were a purposive sample of 30 Kiswahili radio listeners, selected based on diverse demographic characteristics. Since the research area covered Kenya’s capital City County, Nairobi, 357 questionnaires were distributed. There were also radio professionals including 5 lead radio presenters and 5 experienced producers from lead Kiswahili radio stations in Kenya and 5 Key Informants who are experts in media and communication, including academics and industry analysts. The data was analyzed through a combination of qualitative and quantitative approaches. The paper found that factors that made the radio broadcast audience listen include the nature of the content, the timing of the radio broadcast airing, its content and response to real and current health issues, presentation style, simple language, relevant content, appropriate format, likable and knowledgeable expert in the studio, interesting topics, instructiveness with expert, likable production techniques and knowledgeable professionals. The radio broadcasts had many comparatively older people as listeners compared to the youthful, and more men than women listened. To enhance the effectiveness of Kiswahili radio broadcasts, it is recommended that stations diversify their content to cater to various demographic segments, including age, gender, regional differences and education level. Additionally, incorporating audience feedback mechanisms can help tailor programs to listeners' preferences. Investing in digital platforms and social media engagement also broadens reach, particularly among younger audiences.